The Legacy of COVID-19: Na analysis of the main complications and sequelae (Research, Society and Development, 2023)
Introduction: COVID-19 is an acute respiratory infection caused by the SARS-CoV-2 virus and represents a major health problem currently being faced, ranging from mild conditions to death. Individuals who have a more compromised clinical picture may have several sequelae. Objective: To describe the main complications and sequelae associated with post-COVID-19. Methods: This is an integrative review that used data from Pubmed and LILACS databases, limited to the period from 2019 to 2023. The search was carried out by crossing the descriptors “COVID long”, “COVID-19” and “SARS- CoV-2” according to the DeCS to answer the question formulated through the PICO strategy. Results and Discussion: The post-COVID syndrome (PCS) represents the symptomatology present after acute infection with the COVID-19 virus, the condition being defined from 4 weeks or 3 months after the onset of symptoms, depending on the determinations of the health authorities. In the same way as the acute disease, PCS affects several systems butat a later date, with sequels related to the respiratory, cardiovascular, nervous and musculoskeletal systems being portrayed here, involving complications such as pneumonia, pulmonary and cardiac fibrosis, myocarditis, cognitive problems, fatigue, anxiety, depression and myalgias. Conclusion: Simultaneously, SARS-CoV-2 has pulmonary and extrapulmonary actions and, as late complications are still objects of recent study, the results still differ in many points. Thus, it is necessary to develop more research to establish a consensus.